PERTUMBUHAN BIBIT KOPI ARABIKA (Coffea arabica L.) DI MEDIUM GAMBUT PADA BERBAGAI TINGKAT NAUNGAN DAN DOSIS PUPUK NITROGEN - Anita ' '; Gunawan ' Tabrani; Idwar ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT The purpose of this research was to got of arabica coffee seedling growth better which although it is planted on peat medium by shading and Nitrogen fertilizer. This research was carried out at the experimental station, Faculty of Agriculture Riau University on Bina Widya Campus, Simpang Baru Sub-districs, Tampan Districs, Pekanbaru from October 2015 to Januari 2016. This research was done experimentally utilized split plot design based on completely randomized design. The main plot was shading. Which are: without shading, 25% shading, 50% shading and 75% shading. Sub-plot was Nitrogen Fertilization, were: without nitrogen, 9,8 g N/plant (200 kgN/ha) and 19,6 g N/plant (400 kgN/ha). Parameter observed are seedling height, number of leafs, diameter of stalk, root volume, dry weight seedling, leafs and root ratio, the leaf width. The results showed that shading could increase number of leafs, seedling dry weight and the leaf width. Nitrogen fertilizeron peat medium has showed negative effect on seedling height, the number of leaf, diameter of stalk, root volume and seedling dry weight of Arabica coffee seedling.   Keywords: arabica coffea seedling growth, peat medium, shading, nitrogen fertilizer